2005
DOI: 10.1345/aph.1e640
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Clinical Pharmacist on Readmission in Patients with Acute Coronary Syndrome

Abstract: The addition of pharmacists did not decrease readmission in patients with ACS. The finding of significant reduction in readmission in the subset of patients with unstable angina should be considered "hypothesis generating" for future randomized studies to confirm the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…The interventions offered to physicians by clinical pharmacists have the highest acceptance in terms of the resolution and the prevention of DRPs. 41-96 % acceptance has been reported [18][19][20][21]. It was unfortunately not possible to compare this to our study, because the case of not knowing the outcome of the interventions performed were very high.…”
Section: Discussionmentioning
confidence: 64%
“…The interventions offered to physicians by clinical pharmacists have the highest acceptance in terms of the resolution and the prevention of DRPs. 41-96 % acceptance has been reported [18][19][20][21]. It was unfortunately not possible to compare this to our study, because the case of not knowing the outcome of the interventions performed were very high.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, we can only be sure that patients survived to 30 days, as this was the follow-up period in the original analysis of the data. 13 Therefore, if patients had died between 30 days and 12 months after the index hospitalization, our rates of readmission could be skewed. Finally, we were able to account only for patients who were readmitted to our health system.…”
Section: Readmittedmentioning
confidence: 99%
“…This study was a post hoc cohort analysis of a previously published prospective observational study. 13 Patients included in the study came to a 903-bed inner-city Am J Health-Syst Pharm-Vol 63 Feb 15, 2006 tertiary care teaching hospital in a large metropolitan area. The hospital is the referral center and flagship for a major health system.…”
mentioning
confidence: 99%
“…Pharmacists can play a central role in various components, such as patient education and medication reconciliation. 14,15 Medication errors constitute an important risk factor for rehospitalization. Forster and colleagues 16 found that nearly two thirds of postdischarge adverse events were medication related and that 29% of these events were serious or life threatening, sometimes resulting in emergency department (ED) visits and hospital admissions.…”
mentioning
confidence: 99%
“…19,20 In particular, studies have found that medication counseling and reconciliation may reduce 30-day readmission rates. 14,21,22 Pharmacists are increasing their role in patient care interventions, [23][24][25][26][27] including care transition programs, 15,19,21 but more research is needed to assess the impact of such programs.…”
mentioning
confidence: 99%